Adaptive fuzzy control for tendon-sheath actuated bending-tip system with unknown friction for robotic flexible endoscope - Ren, Fan; Wang, Xiangyu; Yu, Ningbo; Han, Jianda (Frontiers in Neuroscience, 2024)
The Tendon-sheath actuated bending-tip system (TAB) has been widely applied to longdistance transmission scenes due to its high maneuverability, safety, and compliance, such as in exoskeleton robots, rescue robots, and surgical robots design. Due to the suitability of operation in a narrow or tortuous environment, TAB has demonstrated great application potential in the area of minimally invasive surgery. However, TAB involves highly nonlinear behavior due to hysteresis, creepage, and nonlinear friction existing on the tendon routing, which is an enormous challenge for accurate control. Considering the difficulties in the precise modeling of nonlinearity friction, this paper proposes a novel fuzzy control scheme for the Euler-Lagrange dynamics model of TAB for achieving tracking performance and providing accurate friction compensation. Finally, the asymptotic stability of the closed-loop system is proved theoretically and the effectiveness of the controller is verified by numerical simulation carried out in Matlab/Simulink. The simulation results demonstrate the superiority of the proposed method to achieve tracking and instant response performance.